PEMANFAATAN CYBER EXTENSION SEBAGAI MEDIA INFORMASI OLEH PENYULUH PERTANIAN DI KABUPATEN BOGOR ( Utilization of Cyber Extension as Information Media by Agricultural Counselor in the District of Bogor) - Abung Supama Wijaya; Sarwititi Sarwoprasodjo; Kudang Boro Seminar (Institut Pertanian Bogor, 2015)
ABSTRACTThis study aims to analyze the characteristics and relations of counselor, obstacle of media use, information seeking phases on Cyber Extension and Cyber Extension utilization. The information stages intended use the theory of information seeking, namely: starting, chaining, browsing, differenciating, monitoring, and extracting. This study is conducted to 61 counselors in the Regent/District of Bogor, originationg from three different BP3K. This study is a quantitative research utilizing questionnaires as the research instrument and applying Spearman rank statistic test to analyze the relation between the characteristics of a counselor, the obstacle of media use for information seeking process, and Cyber Extension utilization. The study results state that the characteristics of a counselor has a definite relation with the information seeking phases on the age and motivation indicators. The obstacle of media use has a definite relation with the information seeking phase, and the information seeking phase in Cyber Extension has a definite and positive relation with the utilization of Cyber Extension. Keywords: Cyber Extension, Information Seeking, Counselor ABSTRAKPenelitian ini bertujuan menganalisis karakteristik dan hubungan penyuluh, hambatan penggunaan media, tahapan pencarian informasi pada Cyber Extension dan pemanfaatan Cyber Extension. Tahapan informasi yang diamksud menggunakan teori pencarian informasi yaitu, starting, chaining, browsing, differentiating, monitoring dan extracting. Penelitian ini dilakukan kepada 61 penyuluh di Kabupaten Bogor yang berasal dari tiga BP3K yang berbeda. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan kuesioner sebagai instrumen penelitian dan menggunakan uji statistik rank Spearman untuk menganalisis hubungan antara karakteristik penyuluh, hambatan penggunaan media untuk proses pencarian informasi dan, penggunaan Cyber Extension. Hasil penelitian menunjukan bahwa karakteristik penyuluh memiliki hubungan nyata dengan tahapan pencarian informasi pada indikator umur dan motivasi. Hambatan penggunaan media berhubungan nyata dengan tahapan pencarian informasi dan tahapan pencarian informasi pada Cyber Extension berhubungan positif dan sangat nyata dengan pemanfaatan Cyber Extension.Kata kunci: Cyber Extension, Pencarian Informasi, Penyuluh